Effectiveness of Structured Teaching Program on Knowledge Regarding Assessment and Treatment of Young Infants Based on IMNCI Guidelines Among Nursing Students - Ms. Jyoti Sharma (Young Nurses Journal of Research, 2026)
Introduction: Reducing neonatal and infant mortality remains a major public health priority, particularly in developing countries like India. The Integrated Management of Neonatal and Childhood Illness (IMNCI) strategy, developed by WHO and UNICEF, provides evidence-based protocols for early detection and management of childhood illnesses. Despite its importance, gaps in nursing students’ knowledge regarding IMNCI guidelines persist, mainly due to limited structured educational exposure. Recognizing this need, the present study aimed to assess the effectiveness of a structured teaching program on the knowledge of nursing students regarding the IMNCI guidelines in a selected nursing college in Lucknow. Enhancing knowledge during the formative academic phase can significantly contribute to building skilled future healthcare providers, ultimately improving child health indicators. Methods: A quantitative pre-experimental study design with a one-group pre-test post-test approach was adopted for this research. A total of 80 nursing students were selected using non-probability purposive sampling. The inclusion criteria consisted of students who were available during the study and willing to participate. A structured questionnaire consisting of multiple-choice questions based on IMNCI guidelines was developed and validated for data collection. The participants first underwent a pre-test to assess their baseline knowledge, followed by the administration of a structured teaching program covering all essential aspects of IMNCI. After a gap of one week, a post-test was conducted using the same questionnaire to evaluate knowledge improvement. Statistical analysis was performed using SPSS software. Descriptive statistics like mean and standard deviation were used for summarizing data, while inferential statistics like the paired t-test and chi-square test were applied to test the hypotheses. Results: The analysis revealed a significant enhancement in the knowledge levels of nursing students after the structured teaching intervention. The mean pre-test knowledge score was 24.11 with a standard deviation of 5.39, which increased to a mean post-test score of 26.34 with a standard deviation of 4.99. The paired t-test showed a t-value of 2.6510 with 79 degrees of freedom, and the p-value was 0.010, which is less than the 0.05 level of significance, indicating a statistically significant difference between pre-test and post-test scores. Thus, the structured teaching program was effective in improving students’ knowledge regarding IMNCI guidelines. Furthermore, the chi-square test was applied to assess the association between pre-test knowledge scores and selected socio-demographic variables. No significant association was found between pre-test knowledge scores and age or. However, a significant association was found between the course of study, prior academic exposure to IMNCI, and attendance at IMNCI workshops or training. Students who had prior exposure and training in IMNCI scored significantly better, suggesting that curriculum integration and workshop participation positively impact knowledge acquisition. Conclusion: The study suggests that effective implementation of IMNCI teaching into the regular nursing curriculum, organizing frequent workshops and seminars, and providing clinical exposure to IMNCI protocols could be effective strategies to prepare nursing students for real-world pediatric healthcare challenges. Given the critical role that nurses play in child health care services, equipping them with evidence-based knowledge and skills during their training years is essential for achieving better health outcomes for infants and children